Behavioural response of the invasive Halyomorpha halys (Hemiptera: Pentatomidae) to host plant stimuli augmented with semiochemicals in the field. (19th April 2017) - Morrison, William R.; Allen, McKenzie; Leskey, Tracy C.
Abstract: Although much work has focused on understanding how the invasive brown marmorated stink bug, or Halyomorpha halys, responds to pheromonal stimuli, very little research has explored the response of H. halys to plant volatiles and other host stimuli. The present study aimed to determine (i) whether more acceptable, less acceptable or unacceptable host plants augmented with plant volatile mixes and/or pheromone can enhance the retention capacity of plants for H. halys in the field and (ii) whether plant volatiles [apple, peach or green leaf volatile (GLV) mixtures] can increase attraction to pheromone‐baited pyramid traps. The presence of the H. halys pheromone was the primary factor in increasing the retention capacity of tagged, released adults to host plants, although plant volatile mixtures added a small increase in retention. Plant species helped to modulate the effectiveness of both the pheromone and additional plant volatiles in retaining individuals. Plant volatiles did not increase attraction of adults to baited pyramid traps and may have inhibited the attraction of nymphs. Overall, the results of the present study suggest that host plant stimuli, construed broadly, are important for the foraging decisions of H. halys, although further research is needed to identify the most effective stimuli.